Effects of Feeder Cells on the Primary Culture of Ovarian Cell Populations from Adult Japanese Medaka (Oryzias latipes) - Jun Hyung Ryu; Seung Pyo Gong (The Korean Society of Animal Reproduction and Biotechnology, 2020)
Fish ovarian germline stem cells (OGSCs) that have the abilities to selfrenew and differentiate into functional gametes can be used in various researches and applications. A main issue to be solved for effective utilization of fish OGSCs is the development of their stable in vitro culture condition, but only few researches about fish OGSC culture have been reported so far. In this study, in order to find the clues to develop the culture condition for OGSCs from Japanese medaka (Oryzias latipes), we tried to establish somatic cell lines as a candidate for the feeder cells and evaluated its supporting effects on the culture of ovarian cell populations from O. latipes. As the results, the somatic cell lines could be established only from the embryonic tissues among three tissues derived from embryos, fins and ovaries. Three embryonic cell lines were tested as a feeder cell for the culture of ovarian cell population and all three cell lines induced cell aggregation formation of the cultured ovarian cells whereas the feeder-free condition did not. Furthermore, a significant cellular proliferation was observed in the ovarian cells cultured on two of three cell lines. As a trial to increase the capacity of the cell lines as a feeder cell that supports the proliferation of the cultured ovarian cells, we subsequently established a stable line that expresses the foreign O. latipes fibroblast growth factor 2 (FGF2) from an embryonic cell line and evaluated its effectiveness as a feeder cell. The ovarian cells cultured on FGF2 expressing feeder cells still formed cell aggregates but did not show a significant increase in cellular proliferation compared to those cultured on non-transformed feeder cells. The results from this study will provide the fundamental information for in vitro culture of medaka OGSCs.